Self- and Co-regulation in Cybercrime, Cybersecurity and National Security - Tropina, Tatiana; Callanan, Cormac; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The ever increasing use of computers, networks and the Internet has led to the need for regulation in the fields of cybercrime, cybersecurity and national security. This SpringerBrief provides insights into the development of self- and co-regulatory approaches to cybercrime and cybersecurity in the multi-stakeholder environment. It highlights the differences concerning the ecosystem of stakeholders involved in each area and covers government supported initiatives to motivate industry to adopt self-regulation. Including a review of the drawbacks of existing forms of public-private collaboration, which can be attributed to a specific area (cybercrime, cybersecurity and national security), it provides some suggestions with regard to the way forward in self- and co-regulation in securing cyberspace.
Foreword -- Public-private collaboration: cybercrime, cybersecurity, national security -- Evolution, implementation and practice of Internet self-regulation, co-regulation and public-private collaboration.
Keywords: Computers -- Law and legislation; Mass media -- Law and legislation; Computer security; Legal Aspects of Computing; IT Law, Media Law, Intellectual Property; Systems and Data Security